Consumer information and price transmission: Empirical evidence - Jens-Peter Loy; Dieter Pennerstorfer; Daniela Proshi; Christoph R. Weiss; Biliana Yontcheva (Johannes Kepler University of Linz, Department of Economics, 2019)
We investigate how consumer information affects price adjustment in the Austrian retail gasoline market. Our measure of consumer information is obtained from detailed census data on commuting behavior, as commuters can freely sample prices on their commuting route and are thus better informed about prices. A threshold error-correction model suggests that prices adjust more quickly if cost shocks exceed certain thresholds. Parametric and semi-parametric regressions show that a larger share of informed consumers increases both transmission speed and pass-through elasticity. Better informed consumers reduce the asymmetry in thresholds, but have no effect on the asymmetry in the speed of adjustment.
Keywords: D43; D83; L13; 330; Price Transmission; Consumer Information; Commuters; Gasoline Market; Threshold Error-Correction Mode